1994
DOI: 10.1007/bf00299111
|View full text |Cite
|
Sign up to set email alerts
|

Selective decontamination of the colon before elective colorectal surgery

Abstract: The controversy over the route of administration of antibiotic prophylaxis in patients undergoing elective colorectal operations persists for oral, parenteral, and a combination of the two routes. The oral antibiotics commonly administered for colorectal prophylaxis, neomycin and eythromycin base, are not absorbed in the gastrointestinal tract (GIT). However, the 4-fluoroquinolones are absorbed in the upper GIT and are excreted in part by the colonic mucosa. Their action is then to remove, or severely depress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 32 publications
0
32
0
2
Order By: Relevance
“…However, neither this nor prior meta-analysis [26] discriminated between non-absorbable and absorbable antibiotics given by the oral route. As a result, two trials, involving a total of 476 patients, were not included in our analysis since they used absorbable oral antibiotics given 1 h prior to surgery [33,34]. Moreover, with our search criteria, we were able to identify 5 additional PRT involving a total of 843 patients that were not included in the most recent Cochrane analysis.…”
Section: Discussionmentioning
confidence: 94%
“…However, neither this nor prior meta-analysis [26] discriminated between non-absorbable and absorbable antibiotics given by the oral route. As a result, two trials, involving a total of 476 patients, were not included in our analysis since they used absorbable oral antibiotics given 1 h prior to surgery [33,34]. Moreover, with our search criteria, we were able to identify 5 additional PRT involving a total of 843 patients that were not included in the most recent Cochrane analysis.…”
Section: Discussionmentioning
confidence: 94%
“…The results demonstrated that the two methods together yielded a 5% rate of surgical site infection whereas the patients who received only systemic antibiotics and no oral antibiotic bowel preparation had a 16% rate of surgical site infection. In this same publication, Lewis identified 12 additional studies where systemic antibiotics were compared to systemic plus oral antibiotics in colon surgery (Table 2) [24][25][26][27][28][29][30][31][32][33][34][35]. The meta-analysis demonstrated marked statistical significance (p Ͻ 0.0001) in favor of lower surgical site infections with combinations of the two methods.…”
Section: Systemic Versus Oral Antibiotics In Colon Surgerymentioning
confidence: 95%
“…Prospective randomized clinical evidence to support the use of preoperative oral antibiotics came from Washington et al [18] in a study where neomycin and tetracycline were shown to reduce surgical site infections from 43% in the placebo group to only 5% in the antibiotic group. Because of the poor activity of tetracycline against anaerobic Bacteroides fragilis, Nichols and Condon introduced erythromycin base as an appropriate antibiotic 9 Penicillin 94 10% 25% Burton (1973) 10 Multiple 100 65% 58% Evans and Pollack (1973) 11 Cephaloridine 87 34% 43% Burton et al (1974) 12 Gentamicin 80 34% 31% Keighley et al (1976) 13 Lincomycin 62 12% 38% Burdon et al (1977) 7 Cephalothin 52 46% 54% 30 Neomycin/erythromycin Cefoxitin Reynolds et al (1989) 31 Neomycin/metronidazole Piperacillin Khubchandani et al (1989) 32 Neomycin/erythromycin Cefazolin Stellato et al (1990) 33 Neomycin/erythromycin Cefoxitin Taylor and Lindsay (1994) 34 Ciprofloxacin Piperacillin McArdle et al (1995) 35 Ciprofloxacin Amikacin/metronidazole Lewis (2002) 23 Neomycin/metronidazole Amikacin/metronidazole to use with the neomycin for intestinal anti-sepsis. Prospective randomized studies demonstrated the utility of the oral antibiotic bowel preparation [19,20].…”
Section: The Antibiotic Bowel Preparationmentioning
confidence: 98%
“…The intention was to remove GNAB and yeasts from the oropharynx and upper and lower gastrointestinal tract using non-absorbable antibiotics, thus reducing colonisation and infection of the tissues by these organisms. The prophylactic use of this strategy has been favourably assessed in cardiopulmonary bypass operations, liver transplantation and colorectal surgery [13][14][15][16]. However, conclusive evidence for the benefit of SDD in any of these settings, or in emergency surgery, is not available and thus this approach is not recommended for routine surgical practice.…”
Section: Selective Decontamination Of the Digestive Tractmentioning
confidence: 99%